(untitled) (Law, State and Telecommunications Review, 2014)
Purpose ”“ While communication technologies become more innovative and Internet grows, the need to review the mandate of the Internet Governance Forum is clearly evident. The purpose of this article is based, then, on research done on globalization and democracy (Chua, 2003), on "trilemmas" of global integration (Rodrik, 2000) and on the logic of collective action (Olson, 1971). Methodology/approach/design ”“ The authors use arguments based on economics, political science and communication theory in order to answer the following question: to what extent is it possible to put into practice a policy for Internet governance? Findings ”“ They conclude, firstly, that States should stick to “thin” globalization of the Internet or choose between sovereignty and democracy. Practical implications ”“ Secondly, they also conclude that the United States, which continues to dominate the Internet, must remain engaged and involved in Internet governance.